2010
DOI: 10.3126/saarctb.v5i1.3079
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Intestinal Protozoan Parasitic Infection in HIV Positive Patient in Jamnagar, Gujarat

Abstract: The case definition of AIDS encompasses a spectrum of infections and malignancies, labelled as opportunistic infections. In recent years, numerous studies have outlined the emergence of opportunistic gastrointestinal protozoa that have caused diarrhoeal illness among HIV - AIDS patients. Purpose of present study was to determine the prevalence of opportunistic intestinal protozoal parasites in HIV positive patients with or without diarrhoea. A total of 100 stool samples of HIV positive patients were examined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Isosporais infrequently associated with diarrhea due to AIDS in the USA and Europe (about 2%), but is commonly isolated in patients with AIDS and chronic diarrhea in Brazil (9.9%), Zaire (12%), Zambia (16%), and Haiti (12%) [24]. Detection rate of Cyclospora in this study found to be 1.0% in HIV patients which correlates with the studies done in Chennai (0.6 %) [23] and in Gujrat (1%) [17]. Higher rates of infection by Cyclospora have been reported by Mohandas et al [14] (3.3%) and Soave R [25] (11%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Isosporais infrequently associated with diarrhea due to AIDS in the USA and Europe (about 2%), but is commonly isolated in patients with AIDS and chronic diarrhea in Brazil (9.9%), Zaire (12%), Zambia (16%), and Haiti (12%) [24]. Detection rate of Cyclospora in this study found to be 1.0% in HIV patients which correlates with the studies done in Chennai (0.6 %) [23] and in Gujrat (1%) [17]. Higher rates of infection by Cyclospora have been reported by Mohandas et al [14] (3.3%) and Soave R [25] (11%).…”
Section: Discussionsupporting
confidence: 86%
“…Difference in the incidence of intestinal protozoal parasitic infection reported by different workers can be attributed to the difference in geographical distribution of parasites, sanitary practices and different selection of cases. Various studies from India and other countries have reported a high prevalence of intestinal parasite, ranging from 25 to 60 percent [11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies from Northern India have found  Cryptosporidium  to be the most common parasite, while the prevalence of  Isospora was found to be much lower [26-27]. Studies from Southern India, on the other hand, reported a higher prevalence of  Isospora belli  rather than Cryptosporidium  [3, 23].…”
Section: Discussionmentioning
confidence: 99%
“…[1315] I. belli was found as the commonest parasite by Gupta at Jamnagar (17.24%) and Kumar at Chennai (18%). [417] Differences in the incidence of intestinal parasitic infections can be attributed to the differences in geographical distribution of parasites, sanitary practices and different selection of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Knowledge of the pattern of opportunistic infections can often guide therapy when resource limitations hamper the exact diagnosis of the etiological agent. [4] HIV/AIDS may not be curable but most of the opportunistic infections can be effectively treated. Prophylaxis against some of these infections will not only prolong the life of an HIV infected individual but also improve the quality of life.…”
Section: Introductionmentioning
confidence: 99%